Supernatural skulpturale Visionen des Körperlichen : sculptural visions of the body - Fritz, Nicole 1969-; Volland, Holger; Lenzen, Manuela (DCV, 2020)
Given the technological developments in biogenetics, man will be in a position in the future to existentially alter everything living, nature, the animal world and the images of man. What will bodies look like in the future? Who or what will we be? In what kind of environment will we live? The exhibition SUPERNATURAL presents responses from the realm of hyper-realistic and realistic sculpture. The forward-looking works not only reflect impacts of the digital revolution and genetic technology on ?post-human? man and the environment, they also illustrate by means of hybrid creations that in our day the borderlines between nature and culture have become fluid. Increasingly, technical innovations also play a role in the development of the latest hyper-realistic sculptures. When the artists perfect their production processes using 3D printing and extend the sculptural limits in the direction of robotics and synthetic biology, for them too, new design possibilities open up that are located somewhere between artefact, biology and technology. Exhibition: Kunsthalle Tübingen, Germany (10.10.2020 - 07.03.2021)
Impressum: Diese Publikation erscheint anlässlich der Ausstellung "Supernatural. Skulpturale Visionen des Körperlichen", Kunsthalle Tübingen, 10. Oktober 2020 - 7. März 2021
Keywords: Geschichte 1990-2020; Natur; Kunst; Technik; Körper -- Motiv; Ausstellungskatalog -- Kunsthalle Tübingen -- 10.10.2020-07.03.2021 -- Tübingen